Immunization Status of Under-five Children in Migrants from Peri urban Areas of Pune - Vaidya, Varsha M; Hanumante, Neeta M; Joshi, Aparna M; Mahajan, Saurabh (National Journal of Community Medicine, 2013)
Introduction: Immunization against common childhood diseases has been an integral component of mother and child health services in India since adoption of the primary health care approach. According to WHO, immunization prevents between 2-3 million deaths every year. The focus of this study is to assess the immunization status of children under five years of age amongst migrant construction and brick kiln workers in three randomly selected periurban areas of Pune. Methods: A community based cross sectional study was carried out in under five children of migrant and brick kiln workers of the randomly selected three sites in periurban areas of Pune. Results: Study showed that only 20 % underfive children were fully immunised, 75% were partially immunized and 5% were not immunized at all. About one- fourth of the partially immunized children were not vaccinated because the mothers of the children forgot to take them for immunization as per schedule. Conclusion: The study highlighted the necessity of specialized efforts to deliver vaccination services to the migrant population.